MECHANISMS THROUGH WHICH ISLAMIC BANKING PROMOTES MICROECONOMIC GROWTH: A THEORETICAL AND EMPIRICAL ANALYSIS - Siti Nur Hidayati; Baiq Hidayatun Nisa; Liawati Liawati (Nurul Jadid University, 2024)
This study aims to analyze the role of Islamic banking in microeconomic development in Sumbawa Regency. Islamic banking, with principles based on Islamic law, has great potential in supporting the development of the microeconomic sector which is the backbone of the regional economy. The research method used is a qualitative approach through a literature study containing theories relevant to the topic raised. This research collects and analyzes literature from various sources such as books, journals, scientific articles, and other related documents. The qualitative approach allows researchers to understand the context, dynamics, and complexity of the role of Islamic banking in microeconomic development in Sumbawa Regency. The results show that Islamic banking not only acts as a capital provider, but also as a strategic partner in increasing the capacity of micro businesses through mentoring and financial education programs.